Effect of Trait Anxiety on Students’ Academic Achievement - Samina Shahab, Samina Malik,Shamsa Aziz (PJE, 2023)
This research inquiry was conducted to probe the consequence of trait anxiety on students’ academic achievement. The research design was descriptive, while the quantitative research approach adopted. The main objectives of the study were to investigate the effects of trait test anxiety on the students’ academic achievement and test out the nature of the effects of trait test anxiety on the students’ academic achievement. 504 students (252 male and 252 female students) of the 10th class were selected as sample through stratified random sampling technique.